Borate glasses with PbO and PbCl2 containing Dy3+ ions - Pisarska, Joanna (Oficyna Wydawnicza Politechniki Wrocławskiej, 2010)
Oxychloroborate glasses containing Dy3+ ions in the B2O3–PbCl2–PbO–Al2O3–WO3 system were studied using X-ray diffraction, Raman, FT-IR, absorption, excitation and luminescence spectroscopy. The results concerning glass preparation, short-range order structure and optical properties are reported. X-ray diffraction analysis evidently indicates that the fully amorphous system was prepared. Coexistence of trigonal BO3 and tetrahedral BO4 units was evidenced by Raman and FT-IR spectroscopy. The electronic states belonging to the 4f9 configuration of trivalent Dy3+ were determined from the absorption and excitation spectra. The luminescence bands at 480, 573 and 662 nm were registered in oxychloride glasses, which correspond to transitions originating from the 4F9/2 state to the 6HJ/2 (J = 11, 13, 15) states of Dy3+.
Optica Applicata, Vol. 40, 2010, nr 2, s. 367-374
Keywords: optyka; glasses; dysprosium ions; optical properties